2000
DOI: 10.1177/146040860000200403
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychiatric effects of trauma on children

Abstract: Even minor physical trauma can lead to significant psychological difficulties in children and adolescents, which are often overlooked. Their immediate reactions include behavioural, emotional and cognitive difficulties. Their thinking about the world can be disrupted, leading to further problems. Initial reactions can have a further knock-on effect, with significant consequences sometimes leading to an impact upon their adult personality. Major disaster plans should include a psychosocial aspect. Immediately f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Shaw [10] notes that children and adolescents may have a higher risk for developing PTSD upon exposure to PTLE than adults. Furthermore, a report of children who witnessed certain PTLE suggested that ''children can experience psychological trauma even when they are physically uninjured'' ( [9,11], p.261). Evidence even exists that children can react to PTLE that are only witnessed indirectly through the media [12,13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shaw [10] notes that children and adolescents may have a higher risk for developing PTSD upon exposure to PTLE than adults. Furthermore, a report of children who witnessed certain PTLE suggested that ''children can experience psychological trauma even when they are physically uninjured'' ( [9,11], p.261). Evidence even exists that children can react to PTLE that are only witnessed indirectly through the media [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…A parent may be unaware of a PTLE in the child's life or underestimate its potential impact. A child's developmental level is an especially important factor in determining his or her response to PTLE [11,17]. On one hand, children who are too young (developmentally and/or chronologically) to fully understand the meaning of dramatic, disruptive events and the associated risks may be protected from strong emotional reactions whereas more cognitively developed children are more likely to be sensitive to the abstract and farreaching aspects of a PTLE.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from PTSD (a well-documented consequence of trauma exposure), previous trauma exposure has also been linked to an increased vulnerability to other forms of psychopathology, including depression, social anxiety, substance abuse, dissociative symptoms, personality disorders, aggressive behaviour, sexual dysfunction, self-mutilation and suicidal tendencies, as well as problems with self-esteem, parenting and an increased risk for later victimization (Allen & Lauterbach, 2007;Bandelow et al, 2004;Bedard-Gilligan et al, 2015;Bolton et al, 2004;Callahan, Price, & Hilsenroth, 2003;Fichter, Goldfeder, Conti, Rooney, & Demaria, 2011;Ford & Smith, 2008;Liebenberg & Papaikonomou, 2010;Munjiza, Law, & Crawford, 2014;Pine, Costello, & Masten, 2005;Seedat, Stein, & Carey, 2005;Stovall-McClough & Cloitre, 2006;Trickey & Black, 2000;Wolf, Reinhard, Cozolino, Caldwell, & Asamen, 2009). In a study conducted by Subramaney (2006) at a South African trauma clinic, it was found that other psychiatric disorders, in particular major depressive disorder, were more frequently diagnosed among patients reporting traumatic stress than PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from PTSD (a well-documented consequence of trauma exposure), previous trauma exposure has also been linked to an increased vulnerability to other forms of psychopathology, including depression, social anxiety, substance abuse, dissociative symptoms, personality disorders, aggressive behaviour, sexual dysfunction, self-mutilation and suicidal tendencies, as well as problems with self-esteem, parenting and an increased risk for later victimization ( Fichter, Goldfeder, Conti, Rooney, & Demaria, 2011;Ford & Smith, 2008;Liebenberg & Papaikonomou, 2010;Munjiza, Law, & Crawford, 2014;Pine, Costello, & Masten, 2005;Seedat, Stein, & Carey, 2005;Stovall-McClough & Cloitre, 2006;Trickey & Black, 2000;Wolf, Reinhard, Cozolino, Caldwell, & Asamen, 2009). In a study conducted by Subramaney (2006) at a South African trauma clinic, it was found that other psychiatric disorders, in particular major depressive disorder, were more frequently diagnosed among patients reporting traumatic stress than PTSD.…”
Section: Introductionmentioning
confidence: 99%